Revestimentos de prata sobre superfícies silanizadas: avaliação de resistência química e adesão bacteriana - Noronha, Victor Teixeira (2017)
In the present work, different types of surfaces were developed, using silicon as substrate. By KOH anisotropic etching, surfaces with different roughness could be obtained. Surfaces with roughness values averaging about 7 nm have resulted in increased adhesion and growth of S. aureus on solid surfaces. Results were obtained through in situ growth analysis by laser scanning confocal microscopy (LSCM). Properties analysis of silver nanoparticle coatings was performed at milimeter scale through large-field imaging by using computational algorithms for data processing. After this, AgNPs coatings were produced from nanoparticles with 4 different types of capping agentes, and surfaces with different functionalizing agents. The type of stabilizing capping agent employed on silver nanoparticles did not influence on distribution and formation of particle agglomerates on the surface. On the other hand, the presence of 80 nm thick-multilayered amino-organosilane film on the surface have resulted on a significant increase in the relative amount of nanoparticles, beyond conferring remarkable stability under liquid media of high ionic strength. Functionalizations with other silanes (phenylsilane and methylphosphonatesilane) did not promote AgNPs adsorption, or chemical stability, in a similar scale to the aminosilane.